To servitize is to (re)position : utilizing a Porterian view to understand servitization and value systems - Rabetino, Rodrigo; Kohtamäki, Marko (Palgrave Macmillan, Cham, 2018)
Drawing on the case of a global servitizing company in the ship power industry, we use a Porterian toolkit for analyzing the implications of industry power and its consequences on firm vertical (re)positioning within the value system. Whereas repositioning has been seen as a way of moving closer to customers and obtaining new competencies, strategic moves aimed at increasing companies’ sphere of influence were neglected. This chapter illustrates how the power approach to repositioning, through different alternative mechanisms, complements the widespread capability view and contributes to value system analysis in servitization.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|